Does Convergence of Accounting Standards Affect Earnings Quality: Evidence from Indonesia - Ferdian, Ilham Ari (2016)
This paper is an empirical analysis of the earnings quality effects of accounting standards convergence to IFRS in Indonesia. I conduct three proxies of earnings quality: income smoothing, discretionary accruals, and timely loss recognition. The time periods of the analysis are 2008-2010 as pre-convergence period and 2012-2015 as the post-convergence period with 245 firms from Indonesian listed firms. Discretionary accruals and timely loss recognition measurements in this study found evidence in decreasing of earnings quality in the post-convergence period compared to the pre-convergence period while another measurement show insignificancy. The evidence is the sample firms in post-convergence period tend to increase income-decreasing earnings management and recognise loss timelier than income in high conservatism accounting.